Analysis and Design of Steel and Composite Structures - Liang, Qing Quan. (London: CRC Press, 2015)
"With numerous practical step-by-step examples to illustrate the analysis and design of steel and composite members and connections, this book provides an integrated and comprehensive introduction to the analysis and design of steel and steel-concrete composite structures. It describes the fundamental behavior of steel and composite members and structures and the latest design criteria and procedures. Each section covers the necessary fundamentals for its respective material, but the integration provides further practical insight not possible in independent textbooks. "--
Keywords: Building, Iron and steel; Composite construction; TECHNOLOGY & ENGINEERING / Structural